Study of axial vibration of a motor-compressor system using operational modal analysis - Mat Dan, Reduan; Putra, Azma; Yahya, M. Farid; Samsubaha, Muhammad Fadzlee; Rashid, Zaini (Tech Science Press, 2023)
A case study of excessive vibration on a motor-compressor system is presented in this paper. After barely two months of operation, the reciprocating compressor motor’s routine monitoring revealed excessive axial vibration amplitude. For this reason, the Operational Modal Analysis (OMA) was carried out in order to identify the primary cause. According to the investigation, one of the harmonic components which was 18 times the motor’s running speed matched with a resonance frequency of 112 Hz. According to OMA study, the motor was vibrating in torsional motion because the compressor’s load had stimulated the entire motor-compressor unit at this resonance frequency. The analysis also demonstrates the bulging effect of the motor shaft’s axial vibration on the motor’s endplate